Safety and efficacy of ciprofol versus propofol for gastrointestinal endoscopy: a meta-analysis - Xi Cheng; Pengyu Zhang; Dan Jiang; Baoxia Fang; Fuchao Chen (BMC Gastroenterology)
Abstract Background The role of ciprofol as a novel anesthetic in gastrointestinal endoscopic surgery is unclear. We conducted a systematic review and meta-analysis to evaluate the efficacy and safety of ciprofol for gastrointestinal endoscopy in patients aged over 65 years and under 65 years, aiming to provide evidence-based information for clinical decision-making. Methods We conducted a search for RCTs(randomized controlled trials) comparing ciprofol and propofol in gastrointestinal endoscopy on databases including PubMed, Embase, Cochrane Library, Web of Science, (China National Knowledge Infrastructure)CNKI, Wanfang, and Vipro Chinese Journal Service up to September 15, 2024. The required information was screened and extracted, and the quality of the included research literatures was assessed using the Cochrane Collaboration risk of bias assessment tool, and Meta-analysis of outcome metrics was performed using Revman 5.4 and Stata software. Results A total of 17 RCTs involving 2800 patients were included, with 1,450 patients in the ciprofol group and 1350 patients in the propofol group. The results of the meta-analysis indicated that there was no statistically significant difference in the sedation success rate or recovery time between the two groups across all age categories. In patients under 65 years old, the induction time of the ciprofol group (MD = 0.41 min, 95%CI: 0.04 min ∼ 0.78 min, P = 0.03) was longer than that in the propofol group. The incidences of hypotension (OR = 0.48, 95%CI: 0.32 ∼ 0.72, P = 0.004), bradycardia (OR = 0.66, 95%CI: 0.49 ∼ 0.87, P = 0.004), injection pain (OR = 0.08, 95%CI: 0.05 ∼ 0.15, P<0.0001), respiratory depression (OR = 0.21, 95%CI: 0.15 ∼ 0.30, P<0.0001), and hypoxemia (OR = 0.29, 95%CI: 0.20 ∼ 0.43, P<0.0001), in the ciprofol group were much lower than those in the propofol group. Conclusion Meta-analysis results indicate that, across various age groups, ciprofol demonstrates a higher safety profile and effectively reduces the incidence of postoperative (ADRs)adverse reactions compared to propofol. However, there is no significant difference in the sedative effects of the two agents. This study categorized elderly patients into subgroups, thereby providing a foundation for the application of ciprofol in gastrointestinal examinations of elderly patients. Consequently, we propose that ciprofol may serve as a safer alternative to intravenous anesthesia compared to propofol; However, this conclusion requires further validation through high-quality studies.